Health anxiety and world assumptions of the society and health care professionals concerning COVID-19 (Annals of Medical Research, 2022)
Aim: This study aimed to review the health anxiety and world assumptions of individuals and health care professionals concerning COVID-19 as well as the factors affecting there too.Materials and Methods: This study is descriptive, cross-sectional, and correlational. The "Personal Information Form (PIF)," "Health Anxiety Inventory (HAI)," and "World Assumptions Scale (WAS)" were used to collect data.Results: 56.6% of the participants were health care professionals. WAS total score differs based on gender, marital status, and educational background criteria (p
Keywords: COVID-19 pandemic; Health anxiety; World assumptions